Financing for a sustainable dry bulk shipping industry: What are the potential routes for financial innovation in sustainability and alternative energy in the dry bulk shipping industry? - George Pangalos (Journal of Risk and Financial Management, 2023)
Environmental, regulatory, and economic exogenous disruptions force companies within the maritime shipping industry to become more sustainable. Financing for implementing the necessary changes is particularly challenging for these companies, considering their narrow margins. With the changes in the shipping industry being intrinsically capital-intensive, funding is a particular issue, as few institutional or individual investors can provide the capital required. This paper investigates the challenges of financing. Drawing from the theory of pecking order on debt and equity, it conceptualizes the relation between the modes of financing for the maritime shipping companies and the nature of the disruptions. Initially, we analyze the various IMO decarbonization regulations, GHG emissions, alternative fuels, and green energy. Moreover, the relationship between fleet operation and management and finance is explored. The paper provides a framework to illustrate from a financial perspective the plethora of challenges and disruptions that have troubled the industry. We then recommend more suitable funding routes for companies to gauge the proper mix of equity and debt levels, bonds, and leverage, based on the company's characteristics, such as size or ESG performance, as analyzed via the lens of corporate financing, along with the nature of the disruption, such as high inflation or geopolitical conflicts. In more detail, the paper focuses on key environmental, social, and governance (ESG) drivers both in the short-term and the long-term within the dry bulk shipping industry: impact investing and ESG factors are driving new investment opportunities and contributing to risk mitigation and long-term investment returns. The most pressing financial and economic questions of the time are wildly extended equity and bond valuations, inflation, and the conundrum most central banks face. Given these uncertainties, from an investment perspective for equity markets, the risk/return outlook for risk assets is skewed to the downside, making a cautious approach prudent for maritime shipping companies.
Keywords: O32; Q01; Q55; Q56; 650; alternative energy; bonds; debt; decarbonization; dry bulk shipping; equity; ESG; finance; green energy; IMO; impact investing; inflation; leverage; maritime shipping; sustainability